Endocardial Notch Signaling in Cardiac Development and Disease. Issue 1 (8th January 2016) - Luxán, Guillermo; D'Amato, Gaetano; MacGrogan, Donal; de la Pompa, José Luis
Abstract : The Notch signaling pathway is an ancient and highly conserved signaling pathway that controls cell fate specification and tissue patterning in the embryo and in the adult. Region-specific endocardial Notch activity regulates heart morphogenesis through the interaction with multiple myocardial-, epicardial-, and neural crest–derived signals. Mutations in NOTCH signaling elements cause congenital heart disease in humans and mice, demonstrating its essential role in cardiac development. Studies in model systems have provided mechanistic understanding of Notch function in cardiac development, congenital heart disease, and heart regeneration. Notch patterns the embryonic endocardium into prospective territories for valve and chamber formation, and later regulates the signaling processes leading to outflow tract and valve morphogenesis and ventricular trabeculae compaction. Alterations in NOTCH signaling in the endocardium result in congenital structural malformations that can lead to disease in the neonate and adult heart.